Dephosphorylation of clustered phosphoserine residues in human Grb14 by protein phosphatase 1 and its effect on insulin receptor complex formation. (25th July 2019) - Taira, Junichi; Yoshida, Keisuke; Takemoto, Misaki; Hanada, Kousuke; Sakamoto, Hiroshi
Abstract : The physical interaction of the human growth factor receptor‐bound protein 14 (hGrb14) and the insulin receptor (IR) represses insulin signaling. With respect to the recruiting mechanism of hGrb14 to IR respond to insulin stimulus, our previous reports have suggested that phosphorylation of Ser 358, Ser 362, and Ser 366 in hGrb14 by glycogen synthase kinase‐3 repressed hGrb14–IR complex formation. In this study, we investigated phosphatase‐mediated dephosphorylation of the hGrb14 phosphoserine residues. An in vitro phosphatase assay with hGrb14‐derived synthetic phosphopeptides suggested that protein phosphatase 1 (PP1) is involved in the dephosphorylation of Ser 358 and Ser 362 . Furthermore, coimmunoprecipitation experiments suggested that insulin‐induced hGrb14–IR complex formation was repressed by the substitution of Ser 358 or Ser 362 with glutamic acid. These findings suggested that phosphate groups on Ser 358 and Ser 362 in hGrb14 are dephosphorylated by PP1, and the dephosphorylation facilitates hGrb14–IR complex formation. Abstract : The physical interaction of human growth factor receptor‐bound protein 14 (hGrb14) with intracellular domain of insulin receptor (IR) suppresses insulin signaling. The present study demonstrated that the phosphate groups on hGrb14 Ser358 and Ser362 can be dephosphorylated by protein phosphatase 1 (PP1), and absence of negative charges on the serine residues facilitated forming of hGrb14‐IR complex. These results suggested that hGrb14‐IR complex formation could be modulated by phosphorylation status of the serine residues.